2006
DOI: 10.1002/erv.696
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neurobiology in adults with anorexia nervosa

Abstract: Objective: Neuroimaging and neuropsychology studies in anorexia nervosa have produced conflicting results due to confounding variables of comorbidity, psychotropic medication, age of onset, states of starvation and the absence of homogenous samples and suitable control groups. The aim of this study is to determine if consistent functional abnormalities of the brain exist in a homogeneous sample of women with anorexia nervosa compared to and controls, and to seek any association between such abnormalities and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
0
19
1
1
Order By: Relevance
“…Firstly, the present study focused on children and adolescents. The vast majority of studies that have shown visuospatial ability and memory deficits in anorexia nervosa have focused on adult populations (Jones, Duncan, Brouwers, & Mirsky, 1991;Kemps, Tiggemann, Wade, Ben-Tovim, & Breyer, 2006;Key, O'Brian, Gordon, Christie, & Lask, 2006;Lopez, Tchanturia, Stahl, Booth, et al, 2008;Lopez et al, 2009;Sherman et al, 2006;Szmukler et al, 1992;Thompson, 1993). Three studies have used a mixed sample of children, adolescents, and adults (Fowler et al, 2006;Hamsher, Halmi, & Benton, 1981;Tenconi et al, 2010), while four have focused on adolescents and adults (Grunwald et al, 2001;Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996;Mathias & Kent, 1998;Tokley & Kemps, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, the present study focused on children and adolescents. The vast majority of studies that have shown visuospatial ability and memory deficits in anorexia nervosa have focused on adult populations (Jones, Duncan, Brouwers, & Mirsky, 1991;Kemps, Tiggemann, Wade, Ben-Tovim, & Breyer, 2006;Key, O'Brian, Gordon, Christie, & Lask, 2006;Lopez, Tchanturia, Stahl, Booth, et al, 2008;Lopez et al, 2009;Sherman et al, 2006;Szmukler et al, 1992;Thompson, 1993). Three studies have used a mixed sample of children, adolescents, and adults (Fowler et al, 2006;Hamsher, Halmi, & Benton, 1981;Tenconi et al, 2010), while four have focused on adolescents and adults (Grunwald et al, 2001;Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996;Mathias & Kent, 1998;Tokley & Kemps, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…There is an even greater body of evidence implicating executive dysfunction (Jones et al, 1991;Duchesne et al, 2004;Holliday, Tchanturia, Landau, Collier, & Treasure, 2005;Steinglass, Walsh, & Stern, 2006;Nakazato et al, 2009;Brogan, Hevey, & Pignatti, 2010;Erzegovesi et al, 2010) and visuospatial processing impairments (Jones et al, 1991;Szmukler et al, 1992;Gillberg, Gillberg, Rastam, & Johansson, 1996;Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996;Mathias & Kent, 1998;Grunwald et al, 2001;Lask et al, 2005;Key et al, 2006). Two comprehensive reviews of the neuropsychological literature (Duchesne et al, 2004;Lena, Fiocco, & Leyenaar, 2004) found a lack of consensus, with no clear patterns in the neuropsychology of AN and no evidence that many of the reported deficits reverse with nutritional rehabilitation.…”
Section: Introductionmentioning
confidence: 92%
“…Chowdhury, Gordon, Lask, Christie, Wigley, & Watkins, 2003;Gordon, Lask, Bryant-Waugh, Christie, & Timimi, 1997) and in adults (e.g. Key, Christie, O'Brien, Gordon, & Lask, 2006;Kojima et al, 2005). Up to 70% of patients at low weight show this abnormality.…”
Section: Introductionmentioning
confidence: 94%